The fast detection of streptavidin based on the initial reaction rate of the binding-induced DNA strand-displacement reaction. Issue 37 (13th September 2016) - Li, Chenxi; Lin, Ruoyun; Li, Tian; Liu, Feng; Li, Na
Abstract : Binding-induced DNA strand-displacement reactions diversify the applications beyond nucleic acids and small molecules. Abstract : Binding-induced DNA strand-displacement reactions diversify the applications of DNA strand-displacement reactions beyond nucleic acids and small molecules. To gain an in-depth understanding of the reaction induced by the biotin-streptavidin interaction, we studied the kinetics of the reaction and established a protein detection method based on the binding-induced strand-displacement reaction rate.